International Bailouts, Moral Hazard, and Conditionality - Olivier Jeanne; Jeromin Zettelmeyer (Center for Economic Studies and ifo Institute (CESifo), 2001)
The large international bailouts of the 1990s have been criticized for differentreasons, in particular for generating moral hazard at the expense of theglobal taxpayer. We argue in this paper that some of these concerns areexaggerated or misleading because international bailouts have no or verylittle cost to the international community and the global taxpayer. Theproblem, in our view, is rather to ensure that the international safety net isnot used as an input into bad domestic policies. This may require a shifttowards ex ante conditionality, in the sense that the availability and size ofofficial crisis lending need to be conditional on government policies beforethe crisis.
Keywords: 330